(untitled) (Applied Biological Research, 2010)
The Jammu & Kashmir State, lying on the Western Himalayas harbours rich biodiversity in macrofungi owing to peculiar physiography and wide variation in agro-climatic conditions. During the survey of mycorrhizae prevailing in conifer-dominated forests of Kashmir four hitherto un-reported macrofungi viz, Bolbitius vitellinus (Pers.: Fries) Fries, Clitocybe nuda (Bull.:Fr.) Bigelow & Smith, Coprinopsis macrocephala (Berk.) Berk.Stroh-Tintling and Tricholoma scalpturatum (Fr.) Quél. were collected. These are reported for the first time from the Jammu & Kashmir State, India.